2009
DOI: 10.1353/csd.0.0078
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Challenges That Threaten to Impede the Academic Success of Academically Underprepared Black Males at an HBCU

Abstract: Historically, education has played a central role in the lives of Blacks. Although Blacks continue their penchant for education, Black males have not fared as well in the educational pipeline. Data for this study emerged from a qualitative investigation of factors that promote success for academically underprepared Black males at a historically Black college and university (HBCU). Although all of the participants persisted to graduation, the participants discussed challenges that threatened to impede their aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…Even if HBCUs are found thoroughly heterogeneous, is figure 1 as a stand-alone model equally effective for both groups? Studies have demonstrated the different experiences and levels of success that tend to differentiate women and men (Gasman 2007b;Harper and Kuykundall 2012;Kimbrough and Harper 2006;Lundy-Wagner and Gasman 2011;Palmer et al 2009;Strayhorn et al 2012). Thus, gendered frameworks may be necessary to capitalize on their differences to create even more beneficial educational approaches.…”
Section: For Researchersmentioning
confidence: 99%
“…Even if HBCUs are found thoroughly heterogeneous, is figure 1 as a stand-alone model equally effective for both groups? Studies have demonstrated the different experiences and levels of success that tend to differentiate women and men (Gasman 2007b;Harper and Kuykundall 2012;Kimbrough and Harper 2006;Lundy-Wagner and Gasman 2011;Palmer et al 2009;Strayhorn et al 2012). Thus, gendered frameworks may be necessary to capitalize on their differences to create even more beneficial educational approaches.…”
Section: For Researchersmentioning
confidence: 99%
“…Researchers have found, for example, that black undergraduate men are less prepared for the rigors of collegelevel work compared to their peers from other racial groups (Bonner & Bailey, 2006;Palmer, Davis, & Hilton, 2009). They also tend to be less engaged than others in college classrooms, clubs and structured campus activities, and enriching educational experiences outside the classroom Underpreparedness and disengagement are often identified as factors that help explain high college-dropout rates.…”
Section: By Shaun R Harper and John A Kuykendallmentioning
confidence: 99%
“…4 Factors such as constrained economic resources, fewer opportunities for academic preparation, and less access to social capital, as well as overt (i.e., ''explicit'') race bias, hinder the advancement of blacks in academic science and medicine. 3,[5][6][7][8] In addition, a large body of theoretically sound, experimentally tested evidence makes a compelling case that the mere existence of race stereotypes leads to unconscious or ''implicit'' bias. 9,10 Implicit bias is prejudice in favor of or against a person or group that functions outside of conscious attentional focus.…”
mentioning
confidence: 99%